Localized surface plasmons in platinum aluminide semi-shells. Issue 1 (29th March 2019) - Shahcheraghi, Nikta; Gentle, Angus; Supansomboon, Supitcha; Keast, V; Cortie, Michael B
Abstract: The dielectric function of the intermetallic compound PtAl2 is assessed and found to be comparable to that of titanium nitride, suggesting that nanostructures of PtAl2 may be suitable for plasmonic devices. In order to probe this further, the optical properties of experimentally produced arrays of nanoscale PtAl2 semi-shells of about 300 nm diameter were examined and compared to the results of numerical simulations. The structures showed a broad localized surface plasmon resonance centered on ∼1.3 eV (∼950 nm), which matched the simulations. Calculations showed that a ten-fold enhancement of the electric field of the incident light will be achieved around the rim of suitably oriented PtAl2 semi-shells. The phase of the oscillation induced by 1060 nm light will be retarded by π /2 relative to the incident light. This is indicative of a resonant condition. These observations suggest that it could be worthwhile to investigate possible applications for this and other intermetallic compounds in nanoscale plasmonic devices.